2019
DOI: 10.1097/gox.0000000000002229
|View full text |Cite
|
Sign up to set email alerts
|

Current Trends in Management of Nonsyndromic Unilateral Coronal Craniosynostosis: A Cross-sectional Survey

Abstract: Background: Although the natural history of nonsyndromic unilateral coronal craniosynostosis has been extensively described, optimal management remains controversial due to lack of Level 1 evidence. This study aims to assess the current state of practice among craniofacial surgeons. Methods: Ninety-four craniofacial surgeons were approached to complete a survey consisting of 15 questions. Data were collected assessing surgeons’ primary surgical indication, timing of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 27 publications
(41 reference statements)
1
21
0
Order By: Relevance
“…Fronto-orbital advancement (FOA) and cranial vault remodeling (CVR) are the standard corrective procedures for UCS (Mesa, Fang, Muraszko, & Buchman, 2011;Moderie et al, 2019;Soleman, Thieringer, Beinemann, Kunz, & Guzman, 2015). Although the optimal timing is not agreed upon, the surgery is typically performed at 8-10 months of age (Moderie et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Fronto-orbital advancement (FOA) and cranial vault remodeling (CVR) are the standard corrective procedures for UCS (Mesa, Fang, Muraszko, & Buchman, 2011;Moderie et al, 2019;Soleman, Thieringer, Beinemann, Kunz, & Guzman, 2015). Although the optimal timing is not agreed upon, the surgery is typically performed at 8-10 months of age (Moderie et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Over many years, different techniques have been developed to treat AP due to non-syndromic UCS, but the lack of quality level evidence supporting a technique's superiority over another has resulted in practical discrepancies. The lack of both evidence-based medicine and agreement between surgeons are regarded as the major obstacles in decision making in UCS management [5].…”
Section: Discussionmentioning
confidence: 99%
“…Premature coronal suture fusion combined with the rapidly expanding infant brain results in the typical AP morphology [5]. UCS produces restriction of regional growth and compensatory expansion of adjacent regions with an evident fronto-orbital dysmorphology [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the golden standard guidelines, children with UCS should be treated surgically, preferably during the first year of life. The main goals of the surgical procedure are to prevent elevated intracranial pressure by expanding the intracranial volume and to reshape the cranial vault to improve the aesthetic appearance (Derderian and Seaward, 2012; Warren et al, 2012; Moderie et al, 2019). Regarding the surgical outcome, in terms of restoring a symmetrical facial appearance, several previous studies have found a poorer outcome and a higher reoperation rate in children with MS-associated UCS (MS-UCS) compared to nonsyndromic UCS (NS-UCS; Cassileth et al, 2001; Thomas et al, 2005; Honnebier et al, 2008; Öwall et al, 2016; Öwall et al, 2019).…”
Section: Introductionmentioning
confidence: 99%